Hindu Rashtra and Bollywood: A New Front in the Battle for Cultural Hegemony - Nivedita Menon (South Asia Multidisciplinary Academic Journal)
This paper examines the weaponization by Hindu right-wing politics of the suicide of a young Hindi film actor in September 2020. It argues that his death was invoked in particular ways to sharpen the attack on the Bombay film industry as part of the larger concerted move by the RSS to control and purge spaces seen as either controlled by “left liberals,” or as syncretic and unamenable to Hindu-Muslim polarization. In the course of this attack, some differences within the Hindutva camp have become evident, a phenomenon this paper examines closely.